Neurobehavioral performance of Indonesian farmers and its association with pesticide exposure: A cross-sectional study - Imelda Nafa Pawestri; Erma Sulistyaningsih (Elsevier, 2021)
Background: Acute and chronic pesticide exposure affect human health. The study aimed to assess the neurobehavioral performance and its association with pesticide exposure factors among Indonesian farmers. Methods: A cross-sectional study was conducted among farmers living in Jember, Indonesia. Basic individual characteristics and pesticide exposure factors were documented using questionnaire-based interviews. The neurobehavioral performance was assessed by the German Q18 questionnaire and the WHO Neurobehavioral Core Test Battery (NCTB) consists of the Digit Span, Digit Symbol, Pursuit Aiming, and Trail making instruments. Data were presented descriptively and analyzed statistically using the chi-square test. Results: As many as 90 farmers were recruited. Most farmers were 45-55 years old and had a normal nutritional status and moderate smokers. The neurobehavioral performance of the farmers was 62.22% normal and 37.78% abnormal. The most common neurobehavioral deficits were short memory, concentration difficulties, excessive fatigue, frequent headache, and tremor. The chi-square test showed that the spraying frequency (p = 0.006), the spraying duration (p = 0.002), the working years (p = 0.013), and the PPE usage (p = 0.022) associated with neurobehavioral performance, but the pesticide types (p = 0.289) and spraying time (p = 0.627) did not associated with neurobehavioral performance. Conclusion: Although most farmers showed a normal neurobehavioral performance, some pesticide exposure factors demonstrated an association with neurobehavioral performance among Indonesian farmers. Multiple approaches including implementation of the regulation, choosing alternative biopesticides, and regular counseling on all aspects of pesticides, their impact on health are recommended to minimize pesticides' negative effects.